Source discrimination of atmospheric metal deposition by multi-metal isotopes in the Three Gorges Reservoir region, China. (September 2018) - Liu, Jinling; Bi, Xiangyang; Li, Fanglin; Wang, Pengcong; Wu, Jin
Abstract: Concentrations of heavy metals, as well as isotopic compositions of mercury (Hg) and lead (Pb), in mosses ( Bryum argenteum ) from the Three Gorges Reservoir (TGR) region were investigated to decipher the sources of atmospheric metals in this region. Higher contents of metals (0.90 ± 0.65 mg/kg of Cd, 24.6 ± 27.4 mg/kg of Cu, and 36.1 ± 51.1 mg/kg of Pb) in the mosses from TGR were found compared with those from pollution-free regions. Principal component analysis (PCA) grouped the moss metals into four main components which were associated with both anthropogenic and natural sources. The ratios of Pb isotopes of the mosses (1.153–1.173 for 206 Pb/ 207 Pb and 2.094–2.129 for 208 Pb/ 206 Pb) fell between those of the traffic emissions and coals. Similarly, the compositions of δ 202 Hg (−4.29∼-2.33‰) and Δ 199 Hg (within ±0.2‰) were comparable to those of the coals and coal combustion emissions from China and India. These joined results of Pb and Hg isotope data give solid evidences that the coal combustion and traffic emissions are the main causes of metal accumulation in the TGR region. Graphical abstract: Image 1 Highlights: Sources of metal deposition were identified using Hg and Pb isotopes. Significant MDF of Hg isotopes was found in the mosses. Mercury and Pb isotopes can corroborate each other. Atmospheric metal deposition derived from coal combustion and traffic emissions. Abstract : Pb and Hg isotopic compositions reveal the predominant contribution of coal combustion and traffic emissions to atmospheric metal pollution in the Three Gorges Reservoir region.